Personal identity narratives of therapeutic songwriting participants following Spinal Cord Injury: A case series analysis. (4th July 2018) - Roddy, Chantal; Rickard, Nikki; Tamplin, Jeanette; Baker, Felicity Anne
Abstract : Context/Objective: Spinal Cord Injury (SCI) patients face unique identity challenges associated with physical limitations, higher comorbid depression, increased suicidality and reduced subjective well-being. Post-injury identity is often unaddressed in subacute rehabilitation environments where critical physical and functional rehabilitation goals are prioritized. Therapeutic songwriting has demonstrated prior efficacy in promoting healthy adjustment and as a means of expression for post-injury narratives. The current study sought to examine the identity narratives of therapeutic songwriting participants. Design: Case-series analysis of the individual identity trajectories of eight individuals. Setting: Subacute rehabilitation facility, Victoria, Australia. Participants: Eight individuals with an SCI; 7 males and 1 female. Intervention: Six-week therapeutic songwriting intervention facilitated by a music therapist to promote identity rehabilitation. Outcome Measures: Identity, subjective well-being and distress, emotional state. Results: Three participants demonstrated positive trajectories and a further three showed negative trajectories; remaining participants were ambiguous in their response. Injury severity differentiated those with positive trajectories from those with negative trajectories, with greater injury severity apparent for those showing negative trends. Self-concept also improved more in those with positive trajectories. Core demographic variables did not however meaningfully predict the direction of change in core identity or wellbeing indices. Conclusion: Identity-focused songwriting holds promise as a means of promoting healthy identity reintegration. Further research on benefits for those with less severe spinal injuries is warranted.